The multiple functions of T stellate/multipolar/chopper cells in the ventral cochlear nucleus - Oertel, Donata; Wright, Samantha; Cao, Xiao-Jie; Ferragamo, Michael; Bal, Ramazan (Elsevier, 2011)
Acoustic information is brought to the brain by auditory nerve fibers, all of which terminate in the cochlear nuclei, and is passed up the auditory pathway through the principal cells of the cochlear nuclei. A population of neurons variously known as T stellate, type I multipolar, planar multipolar, or chopper cells forms one of the major ascending auditory pathways through the brainstem. T Stellate cells are sharply tuned; as a population they encode the spectrum of sounds. In these neurons, phasic excitation from the auditory nerve is made more tonic by feedforward excitation, coactivation of inhibitory with excitatory inputs, relatively large excitatory currents through NMDA receptors, and relatively little synaptic depression. The mechanisms that make firing tonic also obscure the fine structure of sounds that is represented in the excitatory inputs from the auditory nerve and account for the characteristic chopping response patterns with which T stellate cells respond to tones. In contrast with other principal cells of the ventral cochlear nucleus (VCN), T stellate cells lack a low-voltage-activated potassium conductance and are therefore sensitive to small, steady, neuromodulating currents. The presence of cholinergic, serotonergic and noradrenergic receptors allows the excitability of these cells to be modulated by medial olivocochlear efferent neurons and by neuronal circuits associated with arousal. T Stellate cells deliver acoustic information to the ipsilateral dorsal cochlear nucleus (DCN), ventral nucleus of the trapezoid body (VNTB), periolivary regions around the lateral superior olivary nucleus (LSO), and to the contralateral ventral lemniscal nuclei (VNLL) and inferior colliculus (IC). It is likely that T stellate cells participate in feedback loops through both medial and lateral olivocochlear efferent neurons and they may be a source of ipsilateral excitation of the LSO. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Lateral Superior Olive; Auditory-Nerve Fibers; Spatial Receptive-Fields; Stellate Cells; Descending Projections; Response Properties; Discharge Patterns; Octopus Cells; Guinea-Pig; Horseradish-Peroxidase